1965
DOI: 10.1038/icb.1965.24
|View full text |Cite
|
Sign up to set email alerts
|

The Localization of Cytochromes and Carotenoids in Isolated Bacterial Membranes and Envelopes

Abstract: Summary. Examination of oxidized and reduced spectra of isolated membranes (plasma and mesosome membranes) and protoplasmic fractions of the lysozymesensitive Cram-positive bacteria Bacillus Ucheniformk, Bacillus stearothcrmophilus, Micrococcus lysodeikticus and Sarcina lutea, has shown that virtually all of the cytochrome and in addition the carotenoids in the latter two organisms are localized in tbe membranes. Although the membranes isolated from cells of Micrococcus lysodeikticus and Sarcma lutea grown in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1971
1971
1998
1998

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…The localization of other "lipid-soluble" components of the bacterial cell, including carotenoids and menaquinones, has been reported in a number of studies (Matthews and Sistrom, 1959;Salton and Ehtisham-ud-din, 1965;Bishop and King, 1962;Salton and Schmitt, 1967a). The carotenoid pigments have been particularly useful "lipid markers" in studies of membrane isolation, fractionation, and characterization (Salton, 1967b).…”
Section: B Lipids and Lipid-soluble Componentsmentioning
confidence: 94%
“…The localization of other "lipid-soluble" components of the bacterial cell, including carotenoids and menaquinones, has been reported in a number of studies (Matthews and Sistrom, 1959;Salton and Ehtisham-ud-din, 1965;Bishop and King, 1962;Salton and Schmitt, 1967a). The carotenoid pigments have been particularly useful "lipid markers" in studies of membrane isolation, fractionation, and characterization (Salton, 1967b).…”
Section: B Lipids and Lipid-soluble Componentsmentioning
confidence: 94%
“…In fact, cells of M. roseus in which carotenoid biosynthesis was stopped with diphenylamine showed very small amounts of carotenoids but exhibited greater resistance to photodynamic killing than did the pigmented wild-type M. roseus. However, considering that carotenoids are generally associated with either the cell membrane (26) or the cell wall (4,42,44), these pigments may by their interactions alter these structures. Earlier studies demonstrated that the M. roseus cell wall consists of polysaccharides (with galactosamine as the amino sugar), lipids, amino acids, and a peptidoglycan consisting of lysine and alanine (15,32).…”
Section: Discussionmentioning
confidence: 99%
“…Release of mesosomal membrane. Convenient marker molecules for membrane fractions of M. lysodeikticus are the carotenoid pigments (see Salton & Ehtisham-ud-din, 1965). The E446 values for carotenoid absorption correlate directly with dry 1972 weight of membrane in suspensions, and as such offer a convenient method for assaying the concentration ofmembrane in aqueous suspensions.…”
Section: Monitoring Proceduresmentioning
confidence: 99%